Effect of Interplay Between Isotropic Gases on Microstructural Evolution of Single Crystal Diamond. Issue 7 (22nd June 2017) - Jain, L.; Mohapatra, D. R.; Basu, R.; Misra, D. S.; Misra, Abha; Samajdar, I.
Abstract : The surface morphology of the diamond films can be generalized as the step/ledge structures: clear upper ledges followed by lower ledges. An increase in step/ledge population was clearly associated with an increase in 13 C concentration. 13 C concentration and increased step/ledge population also supported developments in 'other' crystallographic orientations. The principal (100) component was split between two near (100) components, often constituting the individual steps/ledges. High resolution EBSD also established the presence of non‐(100) orientations. These were present at the ledge/step boundaries and corners. At lower 13C concentration, their presence was virtually eliminated. Abstract : Homo‐epitaxial (100) single crystal diamond films of different isotopic ( 13 C) compositions were synthesized by micro‐wave plasma chemical vapor deposition. An increase in 13 C concentration (0 to 99%) demonstrated clear developments in microstructures. These are related to changes in: (i) morphology, (ii) residual strain and dislocations and (iii) mesoscopic defects. (i) was mainly through increased presence of steps/ledges and corresponding increase in surface roughness. This was accompanied by significantly higher residual strain and presence/energy of dislocations. 13 C concentration also determined mesoscopic defects: presence of non‐(100) orientations, nature of grain boundaries and micro‐segregations of 13 C and/or CH.A link has been established between various reproducible, experimental observations through stipulated increase in interfacial energy and stresses present at grain boundaries.